Lessons from an online workshop to advance strategic de-implementation of universal BMI surveillance - Natalie Egan; Amanda Raffoul; Jill Kavanaugh; Allegra R. Gordon; Tracy Richmond; S. Bryn Austin (Social Sciences and Humanities Open)
This paper presents proceedings from a workshop organized by the Strategic Training Initiative for the Prevention of Eating Disorders (STRIPED) with support from the Harvard Radcliffe Institute for Advanced Study. Our workshop was designed to facilitate strategic planning towards de-implementation of universal BMI surveillance, given its estimated human costs and iatrogenic effects. Using novel frameworks that draw from (de)/implementation science, a transdisciplinary group of scholars and activists selected two sites of BMI surveillance and strategized towards first steps of de-implementation. By sharing our methods, we hope to facilitate future efforts to foster evidence-based de-implementation efforts targeting BMI surveillance and other public health interventions that have proven to be harmful to health.